2015
DOI: 10.1515/ffp-2015-0010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling forest loss and other land use change dynamics in Ashanti Region of Ghana

Abstract: Forest losses amid land use dynamics have become issues of outermost concern in the light of climate change phenomenon which has captivated the world’s attention. It is imperative to monitor land use change and to forecast forms of future land use change on a temporal and spatial basis. The main thrust of this study is to assess land use change in the lower half of the Ashanti Region of Ghana within a 40 year period. The analysis of land use change uses a combination method in Remote Sensing (RS) and Geographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…Forest LC is generally reported to be decreasing in Ghana by several studies and reports [9,18,33,54,55]. Therefore, the overall net gain of about 23.3% forest LC revealed by our results (Figure 5) as well as the net gains observed within the five-year intervals examined (Table 2) are contrary to previous reports.…”
Section: Changes In Forest Land Covercontrasting
confidence: 99%
See 2 more Smart Citations
“…Forest LC is generally reported to be decreasing in Ghana by several studies and reports [9,18,33,54,55]. Therefore, the overall net gain of about 23.3% forest LC revealed by our results (Figure 5) as well as the net gains observed within the five-year intervals examined (Table 2) are contrary to previous reports.…”
Section: Changes In Forest Land Covercontrasting
confidence: 99%
“…For example, Schueler et al [25] reported 58% deforestation within mining concessions in the then Western Region, which has been divided into the Western and Western North Regions since 2019 (Figure 1). Earlier, Koranteng and Zawila-Niedzwiecki [18] also noted that forest loss was a major issue in the Region, which is the most forested in Ghana. Osei-Wusu et al [61] reported remarkable conversions of protected forests to other land uses in the Sefwi Wiaso District in the new Western North Region.…”
Section: Changes In Forest Land Covermentioning
confidence: 96%
See 1 more Smart Citation
“…Attua and Fisher [6] also used the Markov chain model to predict land use change in the New Juaben municipality of Ghana. Koranteng and Niedzwiecki [25] projected forest loss in the Ashanti region of Ghana using the Land Change Modeler tool, which was embedded in the software IDRISI. Samardžić et al present the incorporation of Support Vector Machines (SVL) into land use modelling [26].…”
Section: Introductionmentioning
confidence: 99%
“…The Conversion of Land-use and its effects (CLUE) is another land-use and land-cover change simulation model that has the geographic component, so it uses location characteristics (terrain, distance to roads population density etc.) [51]. These methods have been extensively used in many other studies, the CLUE model was used in simulating land-use changes in south-central Chile [52], to predicting land-use change and its impact on the groundwater system of Kleine Nete catchment in Belgium [53], and in simulating land-use changes in urban renewal areas in Hong Kong [54].…”
Section: Land-cover Change and Demographic Dynamics In Conakrymentioning
confidence: 99%